Attitude of Para-veterinarians towards Training - A. Suresh Naik , M. Srinivasa Reddy , P. Raghunandan , G. V. Bhaskar Reddy and Alok Bharathi, (Indian Journal of Extension Education, 2016)
Attitude of para-veterinarians towards training and extent of relationship between the socio- psychological profile andattitude was assessed by ex-post- facto research design method in Nalgonda district of erstwhile Andhra Pradesh(presently in Telangana state). Majority of the para-veterinarians belonged to middle age group , intermediate tograduation level of education , medium experience and received medium duration of training. Majority of them hadmedium guidance and supervision,mass media exposure,innovativeness, risk preference, rational decision makingability,achievement motivation,job satisfaction,scientific orientation and were having medium attitude followed by highand low attitude towards training. Except age and experience remaining ten variables i.e innovativeness, risk preference,rational decision making ability and achievement motivation had positive and significant relationship with attitude ofpara-veterinarians towards training. It is attributed that future training activity must be preceded by a realistic assessmentof training needs and also require attitudinal enhancement.